Legal Aspects of Determining Import Tax Rates for Foreign Products Based on WTO Provisions - Wiwik Sri Widiarty; Mohammad Belayet Hossain (Unissula, 2026)
Import taxation has become increasingly important as countries seek to protect domestic industries while complying with the legal framework of the World Trade Organization (WTO). In Indonesia, import taxes function as both a source of state revenue and an instrument for regulating international trade. This study analyzes the international legal framework governing import taxation under the WTO and the General Agreement on Tariffs and Trade (GATT) 1994, examines Indonesia’s legal framework, and evaluates the conformity of Indonesia’s import tariff regulations with WTO provisions. The research employs a qualitative normative legal method using statutory, conceptual, and historical approaches. The legal sources examined include the Agreement Establishing the WTO, GATT 1994, Law Number 7 of 1994 concerning the Ratification of the WTO Agreement, Law Number 10 of 1995 concerning Customs as amended by Law Number 17 of 2006, Law Number 7 of 2014 concerning Trade, and Law Number 17 of 2017 concerning the Protocol to Amend the Marrakesh Agreement. The findings indicate that Indonesia’s import taxation framework is generally consistent with WTO principles of non-discrimination, transparency, legal certainty, and trade facilitation. However, greater regulatory harmonization and consistent implementation remain necessary to strengthen compliance with international trade obligations while safeguarding national economic interests.